Rehabilitative treatment of cleft lip and palate: experience of the Hospital for Rehabilitation of Craniofacial Anomalies/USP (HRAC/USP) - Part 1: overall aspects - José Alberto de Souza Freitas; Lucimara Teixeira das Neves; Ana Lúcia Pompéia Fraga de Almeida; Daniela Gamba Garib; Ivy Kiemle Trindade-Suedam; Renato Yassutaka Faria Yaedú; Rita de Cássia Moura Carvalho Lauris; Simone Soares; Thais Marchini Oliveira; João Henrique Nogueira Pinto (University of São Paulo, 2012)
Cleft lip and palate is the most common among craniofacial malformations and causes several esthetic and functional implications that require rehabilitation. This paper aims to generally describe the several aspects related to this complex pathology and the treatment protocol used by the Hospital for Rehabilitation of Craniofacial Anomalies, University of São Paulo (HRAC-USP) along 40 years of experience in the treatment of individuals with cleft lip and palate.